EKSISTENSI PELAKSANAAN TRADISI POSI BOLA DALAM PERSPEKTIF URF DI DESA MATTONGANG TONGANG KECAMATAN MATTIRO SOMPE KABUPATEN PINRANG [EXISTENCE OF THE IMPLEMENTATION OF THE POSI BOLA TRADITION FROM THE URF PERSPECTIVE IN MATTONGANG TONGANG VILLAGE, MATTIRO SOMPE DISTRICT, PINRANG REGENCY] - Abdullatif, Ahmad; Ramadani, Nia; Isnaeni, Arni; Jelmiati, Jelmiati; Sya'ban, Al Mahdy Nur Muhammad; Karadona, Rosika Indri; Rahmawati, Rahmawati (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
The Posi Bola tradition in Mattongang Tongang Village, Mattiro Sompe District, Pinrang Regency, is a traditional ritual of the Bugis people that has high cultural and spiritual value. This tradition is carried out as a form of request for safety and blessings before moving into a new house. This study aims to evaluate the implementation of Posi Bola from an Islamic legal perspective through the ‘urf approach, which allows for dialogue between local culture and religious teachings. Qualitative research methods were used to collect data through observation, interviews, and documentation. The results of the study indicate that the community has a strong understanding of Posi Bola as a cultural heritage that does not conflict with Islamic principles. This tradition reflects social values such as mutual cooperation, respect for neighbors, and spiritual closeness to Allah SWT. Posi Bola can be categorized as ‘urf sahih, which supports the preservation of local culture without sacrificing faith. The involvement of traditional and religious figures in this procession strengthens the synergy between custom and Islam, making Posi Bola a symbol of cultural identity that is relevant amidst the challenges of modernization.